Do Simplified Drug Regimens Improve Compliance? - Reynolds, Laurence James (My University, 1977)
A PROTOCOL FOR THE DESIGN OF A RANDOMIZED CLINICAL TRIAL IN A FAMILY PRACTICE SETTING IS DESCRIBED. THE TRIAL IS DESIGNED TO TEST IF TWICE A DAY (B.I.D.) ANTIBIOTICS PRODUCED BETTER COMPLIANCE THAN THE STANDARD FOUR TIMES A DAY (Q.I.D.) REGIMENS. THE DISEASE MODELS OF STREPTOCOCCAL PHARYNGITIS AND UNCOMPLICATED URINARY TRACT INFECTION ARE USED BECAUSE OF THEIR SIMILARITY AND BECAUSE THEY ARE COMMON IN THE FAMILY PRACTICE SETTING. COMPLIANCE MEASURES INCLUDE URINE ASSAY FOR ANTIBIOTIC PILL COUNTS AND DROP OUT RATES. COMPLIANCE WILL BE ANALYZED IN RELATIONSHIP TO THE TYPE OF REGIMEN, SIDE EFFECTS AND DISEASE OUTCOME.
Keywords: Medical Sciences; Medical Sciences